Static and dynamic camber behavior of uniaxial and biaxial post-tensioned fully, limited, and partially unbonded pre-stressed concrete slab - Zaki, Rana Ismael; Risan, Hussam K. (Revista de la Construcción. Journal of Construction, 2021)
<span style="font-size: 10.0pt; line-height: 107%; font-family: ’Times New Roman’,serif; mso-ascii-theme-font: major-bidi; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-hansi-theme-font: major-bidi; mso-bidi-theme-font: major-bidi; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">Pre-stressed members in various structures are gaining popularity among engineers in many parts of the world because pre-stressed strands offer better stability, serviceability, economy, aesthetics, and structural efficiency. The profile of the strand greatly influences the tensile strength of concrete. The force exerted by the strand on the concrete counterbalances internal tensile forces. A construction engineer’s principal goal is to build an excellent strength structure without sacrificing agility and cost-effectiveness. This study’s main objective is to model numerically different pre-stressed concrete slabs to understand and predict the upward deflection (camber) behavior of uniaxial and biaxial pre-stressing of unbonded concrete strands in the static and dynamic behavior and the maximum moments of pre-stressed concrete members by considering previous experimental work as a benchmark for validation. Particular emphasis was placed on the unbonded post-tensioned pre-stressed slab parameters that influence the mid-span upward deflections and internal moments in linear and nonlinear crack analysis. This study also investigated the effect of strand profiles, strand areas, number of strands, strand eccentricities, loading types, and level. It looked into full and partial pre-stressing with uniaxial and biaxial pre-stressing directions. The numerical dynamic characteristics in terms of members’ natural frequency with such parameters were found. This study used a finite element numerical model for the analysis of linear and cracked sections and concluded that the upward deflection (camber) of uniaxial and biaxial one-way and two-way partially unbounded pre-stressed concrete slabs is affected by the strand’s profile, area, and number and eccentricity; the loading type and value; and the pre-stressing level in static and dynamic analyses.